Spanning trees of 2-complexes from diagram groups over the construction of semigroup presentation of integers using lifting method - Gheisari, Yousof; Ahmad, Abd Ghafur; Chaharborj, S. Seddigh; Sapar, Siti Hasana; Mohd Atan, Kamel Ariffin (Institute for Mathematical Research, Universiti Putra Malaysia, 2012)
For any given semigroup presentation we may obtain the fundamental group. In this paper we will determine spanning trees for the 2-complexes of the fundamental groups obtained from the union of two semigroup presentations with finite different initial generators using lifting method. The spanning trees will be systematically selected by using lifting method according to the length of words. Also the general formula for all lifts of spanning trees and the number of edges in the spanning trees will be computed.